Ridged terraces – functions, construction and use - Baryła, Anna; Pierzgalski, Edward (Journal of Environmental Engineering and Landscape Management, 2008)
Erosion is considered one of the basic processes, leading to soil degradation and contamination of surface water. Terracing is a technical soil conservation method, generally intended to control surface runoff and soil losses. Ridged terraces are mainly used to control soil erosion but they could also be used as a mean for harvesting of rain water. These terraces divide the slope into smaller hydrographic units, significantly reducing the rout of the runoff, thus affecting water circulation on the slope and in the entire basin. Water, retained by terraces, does not participate in the direct precipitation‐runoff transformation process. As, a result, water resources in a given site are increased. In Poland there is no tradition and experience with the use of ridged terraces, especially as a measure for rain water collecting. This paper describes types of ridged terraces, their functions and typical cross‐sections, as well as methods of calculation of ridged terraces spacing. Kraiginės terasos – funkcijos, konstrukcijos ir naudojimas Santrauka. Aprašytos kraiginės terasos, naudojamos kaip priemonė, sauganti dirvožemį nuo erozijos ir leidžianti reguliuoti vandens cirkuliaciją baseine. Pateikta kraiginių terasų konstrukcijų charakteristika. Lenkijoje tokios terasos beveik nenaudojamos, ir viena iš priežasčių – nėra jų projektavimo pagrindų. Tačiau naudoti šias terasas kaip priemonę nuo erozijos Lenkijoje būtina, kadangi jos klimato sąlygomis nesant augalinės dangos tirpstantis sniegas pavasarį ir gausūs krituliai vasaros metu labai veikia dirvožemį. Kraiginės terasos neleidžia vandeniui nutekėti nuo dirvožemio ar miško paklotės ir leidžia daryti įtaką vandens išteklių formavimuisi. Reikšminiai žodžiai: kraiginės terasos, kontūrų ribos, paviršiaus nuotėkis, vandens erozija. Гребневые террасы – функции, конструкции и использование Peзюме. Представлено значение гребневых террас как мероприятий, используемых для противоэрозионной защиты почв и управления движением воды в водосборе, а также различные виды террас и их конструкции. Гребневые террасы в Польше практически не используются. Одной из причин этого является отсутствие основ их проектирования. Однако применение гребневых террас в качестве противоэрозионных средств в Польше необходимо в связи с тем, что в ее климатических условиях во время весеннего оттаивания снега и летних проливных дождей при отсутствии растительного покрова земли, особенно пахотные, подвергаются эрозии. Благодаря ограничению стока из сельскохозяйственных и лесных угодий с помощью гребневых террас можно активно влиять на формирование водных ресурсов. Ключевые слова: гребневые террасы, эрозия почв, поверхностный сток. First Published Online: 14 Oct 2010